Desenvolvimento de clones de seringueira e sua relação com os indicadores físicos e químicos do solo - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The rubber tree (Hevea brasiliensis) is a native species of the Amazonian biome with great economic importance due to the production of latex that is used to obtain natural rubber. This forest species is an ally in the sustainable development since it can be used in the consortium with other crops, besides helping the soil quality thanks to the deposit of leaves and the capacity to store carbon. Despite being a kind of Brazilian origin, rubber production in the country is not self-sufficient. In order to optimize production and increase areas with rubber trees, it is necessary to seek an increase in productivity with adequate management. The experiment will be carried out at Fazenda Baru farm in the municipality of Palmeiras de Goiás-GO. The soil has been under rubber cultivation since February / 2013, spacing 6 m x 3.3, and the 10 central plants are considered as useful plot, making a useful area of 198 m² with grafted seedlings. The experiment was set up in a randomized complete block design in a 2x3 factorial scheme, considering two levels of the factors, the two types of clones, three types of management (organomineral fertilization with chicken litter, perennial green manure and brushcutter). Physical attributes such as soil density, soil resistance to penetration, moisture and aggregation, and soil fertility were analyzed. The development of the rubber tree clones was evaluated by stem perimeter measurements and tree height. Analyzes of variance and Tukey test were carried out to compare dendrometric data and physical and chemical attributes of the soil in the different treatments applied in the interweaving of the crop. No significant statistical differences were found between the treatments and between the clones in relation to the physical attributes of the soil. However, the soil acidity reduced the use of organomineral and the RRIM 600 clone showed the highest height results.
Keywords: Pedologia; Fertilidade do solo; Heveicultura; Pedology; Soil fertility; Heveculture; CIENCIAS AGRARIAS